Murrayafoline A inhibits inflammatory cytokines in RAW264.7 cells stimulated with LPS and poly (I:C) by targeting the aryl hydrocarbon receptor - Tran, Trang Thu; Cuong, Nguyen Manh; Ha, Nguyen Xuan; Nakahama, Taisuke; Nguyen, Nam Trung (Bangladesh Journal of Pharmacology, 2025)
No abstract